Patient understanding of and participation in infection-related care across surgical pathways: a scoping review. (September 2021) - Mbamalu, Oluchi; Bonaconsa, Candice; Nampoothiri, Vrinda; Surendran, Surya; Veepanattu, Pranav; Singh, Sanjeev; Dhar, Puneet; Carter, Vanessa; Boutall, Adam; Pennel, Timothy; Hampton, Mark; Holmes, Alison; et al.
Highlights: Patient participation in surgical care is associated with improved outcomes. Opportunities exist for patient engagement in infection care in the surgical pathway. Effective patient engagement is needed, particularly in antimicrobial stewardship. ABSTRACT: Objective: To explore the existing evidence on patient understanding of and/or participation in infection-related care in surgical specialties. Method: A scoping review of the literature was conducted. PubMed, Web of Science, Scopus, and grey literature sources were searched using predefined search criteria for policies, guidelines, and studies in the English language. Data synthesis was done through content and thematic analysis to identify key themes in the included studies. Results: The initial search identified 604 studies, of which 41 (36 from high-income and five from low- and middle-income countries) were included in the final review. Most of the included studies focused on measures to engage patients in infection prevention and control (IPC) activities, with few examples of antimicrobial stewardship (AMS) engagement strategies. While patient engagement interventions in infection-related care varied depending on study goals, surgical wound management was the most common intervention. AMS engagement was primarily limited to needs assessment, without follow-up to address such needs. Conclusion: Existing evidence highlights a gap in patient participation in infection-related care in the surgical pathway. Standardization of patient engagement strategies is challenging, particularly in the context of surgery, where several factors influence how the patient can engage and retain information. Infection-related patient engagement and participation strategies in surgery need to be inclusive and contextually fit.